Radar Bone's Strategy in Implementing Media Convergence in the Editorial Process Online Media - Asyarah, Tasya; Unde, Andi Alimuddin; Aziz, Syamsuddin; Syam, Syahrianti (Palakka : Media and Islamic Communication, 2024)
This journal discusses the strategy of Radar Bone in implementing media convergence in the editorial process of online media. This research aims to describe Radar Bone's strategy in news coverage, to find out Radar Bone's strategy in today's digital era and to find out the application of media convergence in the online media editorial process.To obtain answers to the three main problems, the author uses field research methods, namely interviews, observations and documentation with a communication science approach and a sociology approach with data presentation carried out descriptively qualitative, which is a research that produces descriptive data (depiction). The subject of this research is Usman Sommeng as Chief Editor and Daily Editor in Charge, the researcher considers that the Chief Editor has the main role regarding policies related to media convergence. Furthermore, the researcher determined Askar Syam and Herman kahar as the Managing Editor and Legal Editor to be the next informant to find out how the strategy is used in today's digital era and the last informant is Adri and Baharuddin as Radar Bone reporters. The research results show that: First, the strategy carried out by Radar Bone in news coverage is through several stages starting from the planning, organizing, moving, and also monitoring stages.Â